FOREWORD FROM HANDLING EDITOR - 3RD EDITION - Sodri, Ahyahudin (Journal of Environmental Science and Sustainable Development, 2019)
We are delighted to present the 3rd edition of JESSD, published in December 2019. We have selected eight of the best articles for this edition and one invited article from Environmental Science and Sustainable Development topic.